The reckoning - Airth, Rennie, 1935- (Airth, Rennie, 1935- John Madden novel., 2014)
"The Second World War has ended, leaving a bruised and fragile peace. But this tranquillity is threatened when a shocking murder takes place in the Sussex countryside. Before long, police experts discover a link to another, earlier, killing hundreds of miles away. While Scotland Yard detective Billy Styles struggles to find a link between these two murders, a strange twist of fate brings former Detective Inspector John Madden into the investigations. As the victim count rises, it becomes clear that to catch this serial killer Madden, Styles, and young policewoman Detective-Constable Lily Poole must act quickly"--